Apical Surgery: Progress from Resection to Precision Regeneration - Wang, Dan (International Journal of Public Health and Medical Research, 2025)
Apical surgery serves as the primary salvage treatment for persistent periapical lesions following failed root canal therapy (RCT). Over the past decade, this field has undergone a paradigm shift from "blind resection" to "precision intervention" driven by the integration of digital imaging, minimally invasive techniques, bioactive materials, and regenerative strategies. This systematic review summarizes the latest advances in apical surgery, focusing on digital navigation systems, minimally invasive resection technologies, novel retrograde filling materials, and periapical tissue regeneration approaches. We also analyze current clinical challenges and future development directions to provide evidence-based references for endodontic practice. A comprehensive literature search was conducted in PubMed, Embase, and Cochrane Library using keywords including "apical surgery", "endodontic microsurgery", "digital navigation in endodontics", and "periapical regeneration". Relevant studies published between 2018 and 2025 were included, and the final analysis covered 40 high-quality articles (randomized controlled trials, systematic reviews, and prospective cohort studies).